2018
DOI: 10.1016/j.apsb.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Accurate authentication of Dendrobium officinale and its closely related species by comparative analysis of complete plastomes

Abstract: Owing to its great medicinal and ornamental values, Dendrobium officinale is frequently adulterated with other Dendrobium species on the market. Unfortunately, the utilization of the common DNA markers ITS, ITS2, and matK+rbcL is unable to distinguish D. officinale from 5 closely related species of it (D. tosaense, D. shixingense, D. flexicaule, D. scoriarum and D. aduncum). Here, we compared 63 Dendrobium plastomes comprising 40 newly sequenced plastomes of the 6 species and 23 previously published plastomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 56 publications
4
50
0
Order By: Relevance
“…In contrast, here, we found that the length of Bulbophyllum plastid genomes is determined by the contraction and expansion of the SSC due to the independent loss of the seven ndh genes present in this region. The pronounced effect of the gain/loss of ndh genes in the SSC has been previously reported (Chang et al, 2006;Jheng et al, 2012;Kim et al, 2015;Zhu et al, 2018), but only in Zhitao et al (2017) was the influence of LSC, IR, and SSC length on the genome size measured. As a result, they found that variation in LSC length plays an important role in plastid genome-size variation.…”
Section: Discussion Plastid Genome Featuresmentioning
confidence: 56%
See 2 more Smart Citations
“…In contrast, here, we found that the length of Bulbophyllum plastid genomes is determined by the contraction and expansion of the SSC due to the independent loss of the seven ndh genes present in this region. The pronounced effect of the gain/loss of ndh genes in the SSC has been previously reported (Chang et al, 2006;Jheng et al, 2012;Kim et al, 2015;Zhu et al, 2018), but only in Zhitao et al (2017) was the influence of LSC, IR, and SSC length on the genome size measured. As a result, they found that variation in LSC length plays an important role in plastid genome-size variation.…”
Section: Discussion Plastid Genome Featuresmentioning
confidence: 56%
“…Only four of the 10 most-variable markers identified for Bulbophyllum are shared with its sister genus, Dendrobium (trnR-atpA, psbB-psbT, rpl32-trnL, and clpP-psbB). Among the other six regions, two (matK-trnK and trnS-trnG) were identified by Niu et al (2017a;2017c) and Zhu et al (2018), whereas four (atpH-atpI, ccsA-ndhD, psbK-psbI, and trnM-aptE) are reported for the first time here as highly variable in Orchidaceae. Previous markers used in Bulbophyllum analyses proved here not to be highly variable; for example, Smidt et al (2011) used psbA-trnH and trnS-trnG for the Neotropical sections of Bulbophyllum.…”
Section: Hypervariable Regionsmentioning
confidence: 72%
See 1 more Smart Citation
“…The chloroplast genome could distinguish C. indicum from its closely related species and might become a potential superbarcode for the identification of these species 24 . Zhu et al found that the complete plastome sequence dataset had the highest discriminatory power for D. officinale and its closely related species, indicating that complete plastome sequences can be used to accurately authenticate Dendrobium species 25 . The whole chloroplast genome of S. tonkinensis and its hypervariable region, including the most divergent regions (ycf1, ndhF, accD, and rpoC2), which are also the genes containing the most SNP sites, and the six positively selected genes (matK, psbE, psbF, psbM, psaI, and rpl36) could be selected as potential DNA barcodes for identification of species in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The clean reads were aligned to Dendrobium officinale (GenBank accession No. LC348521) (Zhu et al 2018) and assembled by GetOrganelle pipe-line (Jin et al 2018). The assembled chloroplast genome was annotated using DOGMA (Wyman et al 2004), and corrected by Geneious 11.1.15 (Kearse et al 2012).…”
mentioning
confidence: 99%